Latinx literature unbound : undoing ethnic expectation - Rodriguez, Ralph E. (Ralph Edward), 1965- (New York : Fordham University Press, 2018)
Since the 1990s, there has been unparalleled growth in the literary output from an ever more diverse group of Latina/o writers. The extant criticism, however, has yet to catch up with the diversity of writers we label Latina/o and the range of themes about which they write. Little sustained scholarly attention has been paid, moreover, to the very category--Latina/o--under which we group this literature. Latina/o Literature Unbound, thus, begins with a fundamental question "What does it mean to label a work of literature or an entire corpus of literature Latina/o?" From this question a host of others spin out: What does that grouping allow us to see, predispose us to see, and preclude us from seeing? If the grouping--which brings together a heterogeneous collection of people and groups under a seemingly homogeneous label--tells us something meaningful, is there a poetics we can develop that would facilitate our analysis of this literature? In answering these questions, Latina/o Literature Unbound seeks to unbind Latina/o literature from taken-for-granted critical assumptions about identity and theme. It argues that there may be more salubrious taxonomies than Latina/o for organizing and analyzing this literature. Following a neo-formalist interpretive model that privileges reading as a temporal, meaning-making event, the book argues that genre may be a more durable category for analyzing this literature. Finally, Latina/o Literature Unbound suggests some ways in which we might want to proceed as we move forward with future studies of the writing we have come to identify as Latina/o
Introduction : What we talk about when we talk about Latinx literature -- Brown like me? The author-function, proper names, and the rise of fictional nobodies -- Confounding the mimetic : the metafictional challenge to representation -- From where I stand : the intimacy and distance of we and you in the short story -- The lyric, or, a radical singularity in Latinx verse -- Conclusion : Thinking beyond limits.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 26, 2024).
eBooks on EBSCOhost
Keywords: American literature -- Hispanic American authors -- History and criticism; Hispanic American literature (Spanish) -- History and criticism; Latin American literature -- History and criticism; Littérature américaine -- Auteurs américains d'origine latino-américaine -- Histoire et critique; Littérature américaine (espagnole) -- Histoire et critique; Littérature latino-américaine -- Histoire et critique; LITERARY CRITICISM -- Caribbean & Latin American; Hispanic American literature (Spanish); American literature -- Hispanic American authors; Latin American literature; Identity; Latina/o literature; Literary Theory; Metafiction; Neo-Formalism.; Novel; Poetry; Race and Ethnicity; Short Story; Taxonomy; Electronic books; Criticism, interpretation, etc